Marketing Strategies of Tahfizpreneur Products Produced by PTIs in Malaysia (Journal of Entrepreneurship and Business, 2021)
Optimal product marketing strategies are essential to company success. Profit generation is the main goal in covering management costs and increasing competitiveness regularly. The financial constraints of most Private Tahfiz Institutions (PTIs) in Malaysia created opportunities to venture into business and entrepreneurship. The situation generates income for survival instead of completely relying on the government, private sector, charity, and waqf assistance. Hence, the study aims to identify PTI marketing strategies to promote their products. The study performed semi-structured interviews with six chosen PTI founders involved in the marketing of tahfizpreneur products. The interview data were analysed using inductive content analysis. The findings revealed that the PTIs applied four main marketing strategies to promote the respective tahfizpreneur products: (i) direct sales to customers, (ii) printed promotions using brochures and paid newspaper advertisements, (iii) product sales agents, and (iv) electronic digital marketing, such as Facebook Ads, WhatsApp, Blaster, Instagram, YouTube, EQ2U, and Yezza. The various marketing strategies adopted increased consumer access to tahfizpreneur products, which positively impacts the sales of products and services of PTIs in Malaysia.